2023
DOI: 10.31083/j.fbl2803059
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glutathione in Prevention of COVID-19 Immunothrombosis: A Review

Abstract: Immunothrombosis has emerged as a dominant pathological process exacerbating morbidity and mortality in acute-and long-COVID-19 infections. The hypercoagulable state is due in part to immune system dysregulation, inflammation and endothelial cell damage, as well as a reduction in defense systems. One defense mechanism in particular is glutathione (GSH), a ubiquitously found antioxidant. Evidence suggests that reduction in GSH increases viral replication, pro-inflammatory cytokine release, and thrombosis, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 109 publications
0
7
0
Order By: Relevance
“…In obese patients, OxS is associated with diminished GSH levels and decreased GSH/GSSG ratio 597 . Low GSH levels could also increase viral replication, pro-inflammatory cytokine release, endothelial damage, and immune-thrombosis, which is a hyper-coagulative clinical condition that could exacerbate morbidity and mortality in COVID-19 and PASC 598 . Since m -Dys and OxS jointly contribute to both COVID-19 and PASC pathology, nutritional to replenish optimal GSH levels could be a promising strategy to reset HMRD and support patient recovery 582 .…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…In obese patients, OxS is associated with diminished GSH levels and decreased GSH/GSSG ratio 597 . Low GSH levels could also increase viral replication, pro-inflammatory cytokine release, endothelial damage, and immune-thrombosis, which is a hyper-coagulative clinical condition that could exacerbate morbidity and mortality in COVID-19 and PASC 598 . Since m -Dys and OxS jointly contribute to both COVID-19 and PASC pathology, nutritional to replenish optimal GSH levels could be a promising strategy to reset HMRD and support patient recovery 582 .…”
Section: Long-covid/pasc: Precision Nutrition To Reset Virus-induced ...mentioning
confidence: 99%
“…Since IL-6 and TNF-alpha are inflammatory cytokines that increase ROS, their upregulation in COVID-19 leads to increasingly depleted GSH and increasingly high ROS. Previous papers have suggested that this process both damages tissues directly and also contribute to microthrombosis by dramatically increasing ROS, which in turn modifies fibrinogen [ 38 ]. Due to the central role that GSH appears to play in COVID-19, we hypothesized that supplementing endogenous glutathione with L-GSH would interrupt this cycle, which could be evidenced by decreased levels of the previously mentioned cytokines due to reduced ROS.…”
Section: Discussionmentioning
confidence: 99%
“…GSH has been suggested as a means to decrease clot formation in COVID-19 due to its ability to reduce ROS and NO species, which can cause clot formation by modifying fibrinogen, as previously mentioned [ 38 ]. Previous studies have also found that knockout mice for GXP-3, the enzyme that uses GSH to lower ROS, demonstrate increased platelet-induced microthrombosis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that the concomitant use of high-dose glutathione, NAC, antioxidants, and immune support used by patient 3, along with vaccination and boosters, helped mitigate long-term side effects [101,102,202] since the patient never developed symptoms of long COVID despite exposure six times and concomitant infections with overlapping medical problems. Low glutathione levels and associated thiols, including low levels of NAC, have now been published in multiple scientific studies and reviews as being associated with the most severe complications of COVID-19 infection [206][207][208]. Dapsone has also been published as having significant benefits in a small control group of COVID-19 patients with acute respiratory distress syndrome (ARDS), decreasing mortality in COVID-19 patients admitted to the intensive care unit (ICU) [209,210].…”
Section: Discussionmentioning
confidence: 99%